Intestinal microbiota - impact on host health - Alves, Maria José (2020)
At present it is known that in addition to establish and maintain a normal intestinal health, the intestinal microbiota can exacerbate a multitude of diseases, ranging from colorectal cancer to autoimmune and allergic diseases [1]. The interest in studying the human microbiome, its diversity and human-microorganism interactions has been developing in the last years, as such it has been made available immense information in this area.